Transintestinal transport mechanisms of 5-aminosalicylic acid (in situ rat intestine perfusion, Caco-2 cells) and Biopharmaceutics Classification System - Smetanová, Libuše; Stětinová, Věra; Kholová, Dagmar; Kuneš, Martin; Nobilis, Milan; Svoboda, Zbyněk; Květina, Jaroslav (General physiology and biophysics, 2013)
The aim of the study was 1) to estimate permeability of 5-aminosalicylic acid (5-ASA), 2) to categorize 5-ASA according to BCS (Biopharmaceutics Classification System), and 3) to contribute to determination of 5-ASA transintestinal transport and biotransformation mechanisms. The in situ rat intestine perfusion was used as an initial method to study 5-ASA transport. The amount of 5-ASA (released from tablet) transferred into portal circulation reached 5.79 ± 0.24%. During this transport, the intestinal formation of 5-ASA main metabolite (N-ac-5-ASA) occurred. N-ac-5-ASA was found in perfusate both from intestinal lumen and from v. portae. In in vitro Caco-2 monolayers, transport of 5-ASA (10-1000 µmol/l) was studied in apical-basolateral and basolateral-apical direction (iso-pH 7.4 conditions). The transport of total 5-ASA (parent drug plus intracellularly formed N-ac-5-ASA) was linear with time, concentration- and direction-dependent. Higher basolateral-apical (secretory) transport was mainly caused by higher transport of the metabolite (suggesting metabolite efflux transport). Transport of 5-ASA (only parent drug) was saturable (transepithelial carrier-mediated) at low doses, dominated by passive, paracellular process in higher doses which was confirmed by increased 5-ASA transport using Ca2+-free transport medium. The estimated low 5-ASA permeability and its low solubility enable to classify 5-ASA as BCS class IV.
Keywords: intestinální absorpce; Animals; Intestinal Mucosa; Intestines; Intestinal Absorption; Rats, Wistar; Caco-2 buňky; lidé; Intracellular Space; perfuze; střeva; Male; Perfusion; biotransformace; permeabilita; Permeability; krysa rodu Rattus; intracelulární prostor; Biotransformation; mesalamin; Cell Survival; zvířata; mužské pohlaví; viabilita buněk; Caco-2 Cells; Mesalamine; Rats; střevní sliznice; potkani Wistar; Humans